Two beam induction accelerator for generation of neutrons and gamma radiation - Dolbilov, G.V. (Вопросы атомной науки и техники, 2001)
A new scheme of a proton or electron accelerator with a pre-buncher of a driving electron beam and an accelerator of main and driving beams is presented.